2019
DOI: 10.3390/foods8110551
|View full text |Cite
|
Sign up to set email alerts
|

Production and Physicochemical Properties of Starch Isolated from Djulis (Chenopodium formosanum)

Abstract: Djulis (Chenopodium formosanum Koidz.) is an annual fast-growing underutilized pseudo cereal with a high percentage of starch content. In this study, djulis starch was extracted from the flour of dried grains by three different isolation procedures: (1) hydrochloric acid (HCl) isolation procedure (HP); (2) deionized water isolation procedure (WP); and (3) sodium hydroxide (NaOH) isolation procedure (NP), followed by investigation of the physicochemical properties of the isolated djulis starch. The amylose cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Starch was isolated following a modified method of Lu et al [15]. Briefly, E. ferox seeds were ground into slurry with a blender after soaking in distilled water for 5 h. The starch slurry was obtained by sieving on a stainless steel 60 mesh to remove the E. ferox seed coat and fibers.…”
Section: Starch Isolationmentioning
confidence: 99%
“…Starch was isolated following a modified method of Lu et al [15]. Briefly, E. ferox seeds were ground into slurry with a blender after soaking in distilled water for 5 h. The starch slurry was obtained by sieving on a stainless steel 60 mesh to remove the E. ferox seed coat and fibers.…”
Section: Starch Isolationmentioning
confidence: 99%
“…All 16 sequences were treated as comparative sequences, and each sequence was composed of 14 characteristics (entities). The GRGs of 16 comparative sequence, which were calculated according to Equations (2) and (6), are presented in the last column of Table 6. Then, the grey relational analysis user interface was developed accordingly, to perform computer computing instead of manual calculation (Figure 3).…”
Section: Grey Relational Analysismentioning
confidence: 99%
“…This plant has been cultivated mainly in eastern and southern areas of Taiwan (Taitung and Pingtung) as a cereal crop and was previously used for worship purposes and decorations in seasonal festivals by Taiwanese indigenous people (Taiwan aborigines). In recent years, physicochemical and bioactive characteristics as well as preventive healthcare applications of this crop get attention [6]. For instance, Hong et al demonstrated that djulis extract could protect skin from UV-induced damage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chenopodium formosanum Koidz. (djulis) is a unique traditional pseudo-cereal crop native to Taiwan that has been used by the aboriginal people for more than 100 years [ 12 ]. Djulis is commonly used as fermentation materials for making liquor and as an ingredient in bakery products, snack foods or starchy desserts.…”
Section: Introductionmentioning
confidence: 99%